2006
DOI: 10.1007/s11661-006-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of oxidation characteristics and atomic partitioning in platinum and ruthenium bearing single-crystal Ni-based superalloys

Abstract: The elemental partitioning characteristics of advanced single-crystal Ni-base superalloys containing additions of both Pt and Ru have been investigated using atom probe tomography. Detailed microanalysis revealed Ru additions partitioned preferentially to the disordered g matrix, whereas Pt additions tended to partition to the ordered intermetallic g9 precipitates. The stability of the g9 precipitates at elevated temperatures coupled with the subtle changes in elemental partitioning associated with the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This behavior is in agreement with other studies, [18,28,36] which found that Pt preferentially partitions to the c¢ phase and that Ir partitions slightly in preference to the c phase. Vegard's Law states that a solute element (i.e., Pt or Ir) will have a linear effect on the lattice parameter of the solvent material (i.e., c-Ni or c¢-Ni 3 Al), with the slope of the linear relationship defined as the Vegard's Law coefficient.…”
Section: Partitioning Behaviorsupporting
confidence: 93%
“…This behavior is in agreement with other studies, [18,28,36] which found that Pt preferentially partitions to the c¢ phase and that Ir partitions slightly in preference to the c phase. Vegard's Law states that a solute element (i.e., Pt or Ir) will have a linear effect on the lattice parameter of the solvent material (i.e., c-Ni or c¢-Ni 3 Al), with the slope of the linear relationship defined as the Vegard's Law coefficient.…”
Section: Partitioning Behaviorsupporting
confidence: 93%
“…Therefore, PGM-based intermetallics [5][6][7] and superalloys [8][9][10][11][12][13] are under development in several laboratories and their oxidation behavior under high temperature conditions has recently found increased interest. [14][15][16][17][18][19][20] Unfortunately, PGM alloys have substantially higher densities than Ni-based alloys and are rather expensive. Their use will therefore likely be limited to specialty applications.…”
mentioning
confidence: 99%
“…The influence of the ruthenium concentration on the /'partitioning ratio has been debated for a long time and "reverse partitioning", which describes the intensified partitioning of rhenium into the '-phase upon addition of ruthenium, is often given as the only explanation for the ruthenium effect [15,16,[31][32][33][34]. The many different results in literature for a large range of superalloy compositions let us conclude that the "reverse partitioning effect" is probably strongly dependent on the overall alloy composition.…”
Section: Consequences Of Ru Additionmentioning
confidence: 99%